Technical Note: PYRO‐NN: Python reconstruction operators in neural networks. Issue 11 (27th August 2019) - Syben, Christopher; Michen, Markus; Stimpel, Bernhard; Seitz, Stephan; Ploner, Stefan; Maier, Andreas K.
Abstract : Purpose: Recently, several attempts were conducted to transfer deep learning to medical image reconstruction. An increasingly number of publications follow the concept of embedding the computed tomography (CT) reconstruction as a known operator into a neural network. However, most of the approaches presented lack an efficient CT reconstruction framework fully integrated into deep learning environments. As a result, many approaches use workarounds for mathematically unambiguously solvable problems. Methods: PYRO‐NN is a generalized framework to embed known operators into the prevalent deep learning framework Tensorflow. The current status includes state‐of‐the‐art parallel‐, fan‐, and cone‐beam projectors, and back‐projectors accelerated with CUDA provided as Tensorflow layers. On top, the framework provides a high‐level Python API to conduct FBP and iterative reconstruction experiments with data from real CT systems. Results: The framework provides all necessary algorithms and tools to design end‐to‐end neural network pipelines with integrated CT reconstruction algorithms. The high‐level Python API allows a simple use of the layers as known from Tensorflow. All algorithms and tools are referenced to a scientific publication and are compared to existing non‐deep learning reconstruction frameworks. To demonstrate the capabilities of the layers, the framework comes with baseline experiments, which are described in the supplementary material. The framework is available as open‐source software under the Apache 2.0 licence at https://github.com/csyben/PYRO-NN . Conclusions: PYRO‐NN comes with the prevalent deep learning framework Tensorflow and allows to setup end‐to‐end trainable neural networks in the medical image reconstruction context. We believe that the framework will be a step toward reproducible research and give the medical physics community a toolkit to elevate medical image reconstruction with new deep learning techniques.